A general strategy for diversifying complex natural products to polycyclic scaffolds with medium-sized rings - Zhao, Changgui; Ye, Zhengqing; Ma, Zhi-xiong; Wildman, Scott A.; Blaszczyk, Stephanie A.; Hu, Lihong; Guizei, Ilia A.; Tang, Weiping (Nature communications, 2019)
The interrogation of complex biological pathways demands diverse small molecule tool compounds, which can often lead to important therapeutics for the treatment of human diseases. Since natural products are the most valuable source for the discovery of therapeutics, the derivatization of natural products has been extensively investigated to generate molecules for biological screenings. However, most previous approaches only modified a limited number of functional groups, which resulted in a limited number of skeleta. Here we show a general strategy for the preparation of a library of complex small molecules by combining state-of-the-art chemistry – the site-selective oxidation of C-H bonds - with reactions that expand rigid, small rings in polycyclic steroids to medium-sized rings. This library occupies a unique chemical space compared to selected diverse reference compounds. The diversification strategy developed herein for steroids can also be expanded to other types of natural products. Derivatization of natural products is a powerful approach to generate new molecules for biological screenings. Here, the authors employ C-H oxidation and ring expansion methods for the preparation of a library of medium-sized ring skeleta, which occupy a unique chemical space based on chemoinformatic analysis.